2016
DOI: 10.1017/hpl.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Laser diode stacks: pulsed light power for nuclear fusion

Abstract: Laser drivers are an enabling factor to inertial confinement fusion, because laser diodes must be used instead of flash lamps. We discuss the limitations of laser diode arrays and show what steps the industry is taking. The pump power requirements of large-scale projects such as LIFE or HiPER are within reach of semiconductor laser diode assemblies. Pulsed light output powers per laser bars have been around 300 W per bar, as in the Jenoptik 940 nm bars previously used for pumping the Yb:YAG slabs in the DiPOLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several industrial suppliers have publicly reported multi-100 kW diode laser pump modules for high-energy-class laser systems, and a brief summary of current status was recently presented at the 6 th European Advanced Accelerator Concepts (EAAC) workshop [19], collecting input from TRUMPF, due to their role as providers of pumps for DIPOLE [17,20], Leonardo, due their role as providers of pumps for HAPLS [21] and Coherent and Jenoptik, due to their publication record on supply of pumps for high-energy-class systems [22,23]. Other suppliers are also active (e.g.…”
Section: Status Of Industrial Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several industrial suppliers have publicly reported multi-100 kW diode laser pump modules for high-energy-class laser systems, and a brief summary of current status was recently presented at the 6 th European Advanced Accelerator Concepts (EAAC) workshop [19], collecting input from TRUMPF, due to their role as providers of pumps for DIPOLE [17,20], Leonardo, due their role as providers of pumps for HAPLS [21] and Coherent and Jenoptik, due to their publication record on supply of pumps for high-energy-class systems [22,23]. Other suppliers are also active (e.g.…”
Section: Status Of Industrial Diodesmentioning
confidence: 99%
“…In contrast, although the bars in water-cooled QCW stacked arrays can operate with Popt = 400…600 W, the cooling configuration (one water cooler for many 10's of bars) is typically only suitable for use in low-duty cycle operation of around 1%, limiting the achievable repetition rate of the coolers to f = 20 Hz or less. Higher duty cycle operation rates up to 6% are achievable by a properly adapted design, that increases the spacing of the bars (fewer bars and hence less peak power per cooler) [22]. 2D-arrays of rear-edge cooled QCW stacks with emission power in the many 100's of kilowatts are available from several suppliers for build of large systems, with an example shown in Fig.…”
Section: Examples Of Current State Of Technologymentioning
confidence: 99%
“…Commercially available pump sources that can potentially deliver these parameters consist of stacks or arrays of high-energy class diode lasers (HEC-DL) in 1-cm bar format, with each bar combined with a fast axis collimation (FAC) lens. The bars are collected into pump modules, including customised optics for beam shaping and homogenizing [7][8][9][10][11][12]. There are two main configurations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some publications focus on other wavelengths than =940 nm (e.g., =808 nm), but these modules can very likely be modified for similar performance at 940 nm. Also shown is the optical brightness B of the pump, where the emission aperture was either directly taken from the reference or calculated by the authors as in [8] from the emitting area (integrated over all emitters in the module). The solid angle was also calculated following [5], using the lateral and vertical divergences angles with 95% power content.…”
Section: Introductionmentioning
confidence: 99%